2014
DOI: 10.1007/s11738-014-1735-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of partial drying and desiccation on somatic seedling quality in Norway and Serbian spruce

Abstract: Somatic embryo quality is still a problem for many researchers. To improve the efficiency of germination, special procedures are used, such as partial drying of somatic embryos at high relative humidity or desiccation in the presence of supersaturated solutions of salt. In this work, cotyledonary somatic embryos of Norway spruce (Picea abies) and Serbian spruce (P. omorika) were placed on culture media (ME or BM-5) to germinate. We found that after 4 weeks of incubation on these media, hypocotyl and radicle gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Many studies have investigated how the culture conditions during the maturation phase influence a somatic embryo's capability to germinate, including factors such as, osmoticum (Bozhkov and von Arnold 1998; Hazubska-Przybył and Wawrzyniak 2017), abscisic acid (Bozhkov and von Arnold 1998;Montalbán et al 2010;Alvarez et al 2013), redox agents (Stasolla et al 2004;Pullman et al 2015), gelling agents (Klimaszewska et al 2000;Morel et al 2014a;Lelu-Walter et al 2018) and desiccation treatments (Hazubska-Przybył et al 2015;Carneros et al 2017). In terms of N metabolism, studies have suggested that a reduced accumulation of storage protein during maturation can have a negative impact on the quality of the mature somatic embryos, as compared with zygotic embryos (Klimaszewska et al 2004(Klimaszewska et al , 2016Morel et al 2014b).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Many studies have investigated how the culture conditions during the maturation phase influence a somatic embryo's capability to germinate, including factors such as, osmoticum (Bozhkov and von Arnold 1998; Hazubska-Przybył and Wawrzyniak 2017), abscisic acid (Bozhkov and von Arnold 1998;Montalbán et al 2010;Alvarez et al 2013), redox agents (Stasolla et al 2004;Pullman et al 2015), gelling agents (Klimaszewska et al 2000;Morel et al 2014a;Lelu-Walter et al 2018) and desiccation treatments (Hazubska-Przybył et al 2015;Carneros et al 2017). In terms of N metabolism, studies have suggested that a reduced accumulation of storage protein during maturation can have a negative impact on the quality of the mature somatic embryos, as compared with zygotic embryos (Klimaszewska et al 2004(Klimaszewska et al , 2016Morel et al 2014b).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…In the case of Norway spruce, high initiation rates and recovery of embryogenic tissues from cryopreservation have been observed in previous studies (see, e.g., Nørgaard et al 1993;Klimaszewska et al 2001b;Varis et al 2017). The efficiency of somatic embryogenesis has been greatly improved, e.g., by initiating embryogenic tissues from immature zygotic embryos, manipulating the concentration of plant growth regulators and chemical composition of the culture medium (Hakman et al 1985;Klimaszewska and Smith 1997;Bozhkov and von Arnold 1998;Stasolla and Yeung 2003;Klimaszewska et al 2007;Hazubska-Przybył et al 2015;Varis et al 2017). Various methods concerning the germination, acclimation and selection of emblings have been introduced to improve propagation efficiency (Högberg et al 2001(Högberg et al , 2003Varis et al 2014;Llebrés et al 2018a, b).…”
Section: Introductionmentioning
confidence: 76%
“…In addition, the higher survival of shorter cotyledonary embryos in Paper I may also be an indication of too long a maturation period, which has been reported to decrease embling survival in later phases of SE (Morel et al 2014). Shorter maturation treatments have already been applied in different SE protocols in Norway spruce (see, e.g., Bozhkov and von Arnold 1998;Högberg et al 2001;Hazubska-Przybył et al 2015).…”
Section: Yield Survival and Height Growth After Improvements (Papersmentioning
confidence: 99%
“…These changes are associated with the changes in water content, which could be of interest for further studies because the fact that partial drying of somatic embryos at high relative humidity or desiccation in the presence of supersaturated solutions of salt is used to improve the efficiency of germination. Hazubska-Przybyl et al found that ESEs of Norway Spruce used in this study react on the heat stress and their behaviour differed from other ESEs [ 29 ]. During the first four weeks of cultivation, the ESE cluster seemed to be compactly aggregated; thereafter, the differences between the 1 H nuclei concentration in the inner and outer clusters were more evident.…”
Section: Resultsmentioning
confidence: 99%